Quality indexes based on water measurements for low and medium energy x‐ray beams: A theoretical study with PENELOPE. Issue 1 (9th December 2013) - Chica, U.; Anguiano, M.; Vilches, M.; Lallena, A. M.
Abstract : Purpose : : To study the use of quality indexes based on ratios of absorbed doses in water at two different depths to characterize x‐ray beams of low and medium energies. Methods : : A total of 55 x‐ray beam spectra were generated with the codes XCOMP5R and SPEKCALC and used as input of a series of Monte Carlo simulations performed with PENELOPE, in which the percentage depth doses in water and the k Q, Q 0 factors, defined in the TRS‐398 protocol, were determined for each beam. Some of these calculations were performed by simulating the ionization chamber PTW 30010. Results : : The authors found that the relation between k Q, Q 0 and the ratios of absorbed doses at two depths is almost linear. A set of ratios statistically compatible with that showing the best fit has been determined. Conclusions : : The results of this study point out which of these ratios of absorbed doses in water could be used to better characterize x‐ray beams of low and medium energies.